Exosomal proteases in colorectal cancer - E. A. Zambalova; M. R. Patysheva; A. A. Dimcha; S. N. Tamkovich; A. E. Grigor’eva; E. S. Kolegova; I. V. Kondakova; S. G. Afanas’ev; N. V. Yunusova (Успехи молекулярной онкологии, 2019)
The objective is to evaluate the level of ADAM10 and ADAM17 (a disintegrin and metalloproteinase) proteases, as well as 20S-proteasomes in blood plasma exosomes of patients with colorectal cancer.Materials and methods. The study included 60 patients with colorectal cancer (T2–4N0–2M0–1) and 10 control patients. The material for the study was EDTA blood plasma. Exosomes of blood plasma were isolated by ultrafiltration with ultracentrifugation. The level of tetraspanin-associated (ADAM10 and ADAM17) and tetraspanin-non-associated (20S-proteasome) proteases was evaluated by flow cytometry and Western blotting.Results. A twice negative subpopulation (ADAM10–/ADAM17–) predominated in blood plasma exosomes of colorectal cancer patients and control patients. The level of ADAM10+/ADAM17– exosomes was significantly higher in the exosomes of the plasma of control patients. There were no significant differences between the ADAM10/ADAM17 subpopulations and the 20S-proteasome level, depending on sex, age and tumor grade. A decrease in the ADAM10+/ADAM17– subpopulation was found in patients with metastatic colorectal cancer with hematogenous metastases compared with patients with T2–4N1–2M0 and 20S-proteasome compared to T2–4N0M0. A decrease in ADAM10–/ ADAM17+ exosomes and 20S-proteasomes level was found in exosomes of patients with colorectal cancer with a metabolic syndrome  in comparison with patients without metabolic disorders.